-3a-4=5

Simple and best practice solution for -3a-4=5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3a-4=5 equation:



-3a-4=5
We move all terms to the left:
-3a-4-(5)=0
We add all the numbers together, and all the variables
-3a-9=0
We move all terms containing a to the left, all other terms to the right
-3a=9
a=9/-3
a=-3

See similar equations:

| 2x+6=-48 | | 386=l+221 | | (x+6)2=225 | | 15s=840 | | y*2+13y-30=0 | | 15=1.5(t | | 2x+23=10x-3 | | 10g-4g-5g=7 | | 19s=969 | | 1.5+0.5=j | | 21p=378 | | 19h-7h-h-8h+3h=12 | | −35=−5(x−6) | | 2x–7+3x=4x+2 | | x*16-289=x*6-9 | | 4×5x=94 | | x*2-6x+27=0 | | 5y/9=8/3 | | P-p+4p-3p=10 | | 3n-15=7n+9 | | (1/6)^y=36 | | 3(-2)-5y=-21 | | 2(5y-2)+2(y+11)=42 | | (1.07)^x=(10000/500) | | 20x+6=1.4 | | 7=4b=3 | | 7(3x6)+(x+2)=11 | | 42x+x^2+400=0 | | 7(3x66)+(x+2)=11 | | 2x-42=-14 | | 5x+12=2x–15 | | 5x*5=2*2 |

Equations solver categories